PENGARUH PENYULUHAN TENTANG MENU SEIMBANG BALITA TERHADAP KENAIKAN BERAT BADAN BALITA USIA 3-5 TAHUN DI DESA BEDAYUTALANG LUMAJANG - Nisak, Novi Khoirotun; Sary, Yessy Nur Endah; Zakiyyah, Muthmainnah (NHM PRESS, 2023)
The importance of a balanced menu for toddlers to mothers, consumption patterns and nutritional status of toddlers in Bedayutalang Village Lumajang. The purpose of this study was to determine the effect of counseling about a balanced menu for toddlers on weight gain for toddlers aged 3-5 years in Bedayutalang Village, Lumajang.. The research design was a Quasi Experiment with a one group approach in which body weight was measured before and after. the statistical test used the paired sample t-test because the knowledge data on the mother's knowledge was normally distributed after the normality test was carried out using the Kolomogorov. The statistical test results showod that the t-value was -8.644, with a p-value of 0.000 <0.05. In this study, the average value before was 58.2 and the average value after was 84.5. So that there is an influence of counseling about a balanced menu for toddlers on weight gain for toddlers aged 3-5 years in Bedayutalang village, Lumajang.